What’s the Inside Scoop? Challenges in the Supply and Demand for Information on Employers - Sockin, Jason; Sojourner, Aaron (Journal of Labor Economics, 2023)
Workers struggle to understand prospective employers. Through experienced workers’ volunteered reviews, Glassdoor is a platform seeking to provide information about prospective employers to job seekers. We find that the content most valuable to job seekers (negative information) is the kind most risky to supply, pointing to a catch-22. Higher ratings increase job applications to smaller firms only, creating an incentive for them to discourage negative reviews. Concerns about employer retaliation discourage negative reviews and motivate employees who do disclose to conceal aspects of their identity, degrading the information’s value. Reputation institutions provide valuable but partial solutions to workers’ information problems.